GAMBARAN TENTANG KECERDASAN INTERPERSONAL GURU TAMAN KANAK-KANAK SE KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI - Icha Akfani Eliza Akfani Eliza Eliza; Wusono Indarto Indarto; Hukmi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract. This study aims to determine the intelligence picture of the kindergarten teacher  Benai District of Kuantan District Singingi. The benefits of this research is to give input to the interpersonal intelligence to know, can be used as input for the development of learning activities and to improve the quality of education. In terms of theoretical provide information about teacher interpersonal intelligence. The population in this study was overall a kindergarten teacher Benai District of Kuantan District Singingi. Sampel used is saturated samples. The data collection was carried out research on the teaching semester 2014/2015, through the instrument of data collection in the form of a questionnaire sheet. The results showed that of the 8 sub-indicators as a whole is in good category with an average of 78.44%. While Kindergarten Teacher Interpersonal intelligence  Benai District of Kuantan Singingi are in two categories of good and very good. The sub-indicator beada in both categories are sub-indicators of the second with an average of 76.16%, the third sub-indicator with an average of 69.39%, the fifth sub-indicators with an average of 75.55%, with the average seventh sub-indicators -rata 78.78%, and sub-indicators of the eighth with an average of 76.96%. While the sub-indicator mempeoleh excellent category is sub-indicators first with an average 83.43%, the fourth sub-indicators with an average 81.41%, and sub-indicators sixth with an average of 82.42%. Keyword: Interpersonal Intelligence